Pembuatan Sabun Cuci Piring dari Minyak Jelantah di Kelurahan Kemuteran, Gresik, Jawa Timur - Achmad, Achmad Rahditya; A., Syasmitha Lucky; A., Rahma Dea R.; M., Annisa Rachma; K., Dwi Nur Arinal (Jurnal ETAM, 2024)
Waste cooking oil, known as "Minyak Jelantah," originates from frying oils derived from processed vegetable ingredients such as palm oil, corn oil, vegetable oil, and others. Eateries in the Kemuteran Subdistrict consistently use frying oil as the main ingredient in their cooking processes, leading to issues with the generated waste. A viable solution involves utilizing used oil for the production of dishwashing soap. The finished dish soap not only helps reduce waste but also holds higher market value compared to selling used oil to collectors. Additionally, the dish soap product can be used personally and sold, providing broader economic benefits. Overall, this initiative has successfully fostered a positive atmosphere among residents, encouraging the exchange of ideas and knowledge regarding environmentally supportive practices.